Current Trends in the Development of Neuroscientific Research in Education - KhramovaMarina V. Khramova; HramovAlexander E.; Fedorov Alexander A. (Voprosy obrazovaniya / Educational Studies Moscow, 2023)
Modern neuroscience is making significant progress in the study of brain functions, which can be of great importance for the education. However, there is a gap between current neuroscientific evidence on how the brain learns and its direct application in classrooms. What can neuroscientists, psychologists, and educators do to improve the interaction between neuroscience and education? In this article, we attempt to answer this question by examining the essentials of educational neuroscience as an interdisciplinary field of research at the intersection of neuroscience, pedagogy, and cognitive science, which seeks to translate research on the neural mechanisms of learning into educational practice and understand the impact of education on the learner’s brain. In the first part of the article we describe the origins and current progress of neuroscience in education, discuss terminological uncertainty in the Russian scientific literature on the relationship between neuroscience and education, as well as possible and, in our opinion, most promising ways of interaction between psychology, pedagogy and neuroscience. In the second part of the article we analyze the main directions of contemporary research in the field of neuroscience, based on the Scopus database of scientific information.